Urban Commons: Reestablishing Social Ties in African Cities - (:unkn) unknown (My University, 2023)
This chapter examines commons that have emerged in urban settings as one expression of these social, economic, political, and spatial phenomena. Its analysis draws on interviews with the stakeholders of urban commons in Sub-Saharan Africa, as well as a review of the academic literature and documentary research (websites and social networks, local and international media).
Keywords: African Research